Police and Crime Commissioners: new agents of crime and justice policy transfer? - Bainbridge, Laura (Policing and society, 2021)
This article argues that the police accountability and governance reforms introduced by the Conservative-Liberal Democrat Coalition Government (2010–2015) have created a new window for ‘international-subnational’ crime and justice policy transfer to occur in England and Wales by placing Police and Crime Commissioners (PCCs) into a local strategic leadership position. It begins by providing an account of the emergence of PCCs and the controversies that have surrounded them, while at the same time maintaining that they are unlikely to be abolished in the foreseeable future. Three reasons as to why PCCs may seek to import policies from abroad are then presented, encompassing ballot-box politicking, hyper-awareness of constituency discontent and a demonstrated willingness to pioneer new crime control initiatives. Subsequent to presenting an international-subnational policy transfer case study - that of London’s Compulsory Sobriety Pilot - several analytical and practice-based ‘lessons’ are outlined pertaining to the process of emulating non-indigenous subnational crime control innovations.